The biological characteristics and distribution of the greenbug, Schizaphis graminum, and Russian wheat aphid, Diuraphis noxia (Hemiptera: Aphididae), in Argentina and Chile - Clua, Ariel Adrián (2004)
The aphids Schizaphis graminum (Rondani) (greenbug) and Diuraphis noxia (Mordvilko) (Russian wheat aphid, RWA) were collected from several localities in Argentina and Southern Chile. Clones were established from aphids collected at each location. The host preferences were studied in free choice tests. Biotypes were characterized on the basis of aphid antibiosis and host plant tolerance. The production of sexuals was assessed under natural conditions, from March to November in 1997-2001, at La Plata (34°55′ S, 57°57′ W). The greenbug distribution ranged from 24°40′ to 43°28′ S, and was bounded between isothermals 18-20°C and 8-10°C, and isohyets 400-600 mm and greater than 1200 mm. The aphids at all localities were collected from a wide range of cultivated and wild hosts. The biotypes in ten out of thirty-four populations were identified. One population was obligatorily parthenogenetic, the remainder cyclically parthenogenetic. No correlation was found between the region they came from and the period required for the induction of sexuals. RWA was found between 26°50′ and 43°28′S, bounded by the isothermals 20-22°C and 8-10°C, and isohyets 400-600 mm and 2000 mm. In Chile, this aphid was only found in Osorno County, which lies on isothermal 8-10°C and is bounded by the isohyets 1 000 mm and 2000 mm. Only a few RWA genotypes (clones) produced sexuals irrespective of the host they were collected from, period of the year, region, current host, or the day length and average temperature of the rearing conditions. For the first time, RWA was found infesting cultivated as well as wild oats in South America. At low latitudes, populations of both aphid species were found only infesting wild Sorghum halepensis (L).